Analisis Sektor Pertanian dan Kemiskinan Studi Kasus Prevalensi Stunting di Sulawesi Utara - Montolalu, Maya Hendrietta; Tangkere, Ellen Grace; Timban, Jean Fanny Junita; Kaban, Maelani Ai (Jurnal Manajemen STIE Muhammadiyah Palopo, 2024)
Abstract This study aims to find the relationship between the agricultural sector and the prevalence of stunting. This study will look at how much the agricultural sector contributes to reducing cases of stunting in children in several districts in North Sulawesi. Whether or not the agricultural sector has an effect on reducing the prevalence of stunting is still a question in this study. In addition, this research is also related to the second priority of food, nutrition, and stunting prevention which is part of UNSRAT's Strategic Plan. The results of this study are also expected to contribute to policies taken by local governments in overcoming food security problems, especially in handling cases of stunting in children through the agricultural sector. The data collected during 2018-2023 will be analyzed using the IBM SPSS Statistics Version 26 software program and will be estimated using a multiple regression model using two stage least square. The data will be collected from relevant institutions such as BPS (Central Bureau of Statistics) and RISKESDAS (Basic Health Research). The resulting model will be used to describe the most appropriate policy for the current situation in North Sulawesi. The results obtained that food insufficiency affects stunting prevalence are the number of poor people and average rice production. This shows the role of the agricultural sector in fulfilling food needs, thus indirectly contributing to stunting prevalence.Keywords: Agriculture Sector, Food Security, StuntingAbstrak Penelitian ini bertujuan untuk menemukan hubungan antara sektor pertanian dan prevalensi stunting. Penelitian ini akan melihat seberapa besar kontribusi sektor pertanian dalam mengurangi kasus stunting pada anak di beberapa kabupaten di Sulawesi Utara. Apakah sektor pertanian berpengaruh terhadap penurunan prevalensi stunting atau tidak, masih menjadi pertanyaan dalam penelitian ini. Hasil penelitian ini juga diharapkan dapat memberikan kontribusi terhadap kebijakan yang diambil oleh pemerintah daerah dalam mengatasi masalah ketahanan pangan khususnya dalam penanganan kasus stunting pada anak melalui sektor pertanian. Data yang dikumpulkan selama tahun 2018-2023 akan dianalisis dengan menggunakan program software IBM SPSS dan akan diestimasi dengan menggunakan model regresi berganda dengan menggunakan two stage least square. Model yang dihasilkan dari estimasi ini akan digunakan untuk menggambarkan kebijakan yang paling sesuai dengan situasi saat ini di Sulawesi Utara. Hasil yang diperoleh bahwa jumlah penduduk miskin dan rata-rata produksi berpengaruh tidak langsung terhadap stunting prevalence. Hal ini menunjukkan peran sektor pertanian dalam pemenuhan kebutuhan makanan, sehingga secara tidak langsung turut berkontribusi secara tidak langsung terhadap stunting prevalence.Kata Kunci: Sektor Pertanian, Ketahanan Pangan, Stunting